Pendampingan Masyarakat dalam Digitalisasi Pembukaan Rekening Syariah bagi Penerima Bantuan Subsidi Upah - Rahayu, Vidiya; Bachtiar, Arief; Perdana, Putra (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
The digital era has driven significant transformation in the financial system, one of which is through the digital financial migration strategy in the Wage Subsidy Assistance (BSU) program. This community service describes the implementation of the digital financial migration strategy through assistance in opening accounts for BSU recipients at Bank Syariah Indonesia (BSI) KCP Mojokerto Surodinawan. A descriptive qualitative method was used, involving direct observation and semi-structured interviews with BSU recipients categorized as unbanked and underbanked. The results of the community service initiative indicate that the BYOND by BSI application was used as the primary medium for opening digital accounts. However, its implementation still faces challenges related to literacy and technological adaptation among customers. Based on the assistance provided, it was recorded that 60% of BSU recipients experienced difficulties in operating the BYOND application, particularly during the activation stage and when using initial features. The BSU program not only functions as a means of distributing social assistance but also as a catalyst for expanding Islamic financial inclusion. These findings emphasize the importance of a humanistic and adaptive approach in digital financial migration to achieve an inclusive and sustainable economic transformation. The implications of this community service form the basis for Islamic financial institutions in designing digital strategies that are more responsive to the needs of low-income communities as well as unbanked and underbanked groups.